Enhancing English Language Skills Through Gamification: A Case Study at Umm Al Quwain University - Amany Abdel-Ghany Al-Sabbagh (International Journal of Instructional Technology and Educational Studies)
This research investigates the effectiveness of gamification strategies in enhancing English language skills among first-year students in the College of Business Administration at Umm Al Quwain University, United Arab Emirates. The study encompasses a comprehensive assessment of language learning, including speaking, listening, reading, and writing skills, and adopts a dual perspective by considering both teacher and student feedback.The research findings reveal significant positive impacts of gamification on English language learning. After the implementation of gamification, student motivation increased by 93%, driven by a competitive gaming environment. Speaking skills improved by 100%, breaking down barriers to speaking English in public. Listening skills advanced by 86.7% due to diverse daily media within the game, while writing skills improved by 73.3% through daily writing assignments. Additionally, reading skills saw an 80% enhancement, attributed to the inclusion of various articles within the game. Furthermore, the gamification approach facilitated the acquisition of a greater vocabulary and information, underscoring its efficacy in promoting engaging and effective learning experiences.The research recommends raising awareness through seminars and workshops among course designers about the benefits of gamification in education. Furthermore, integrating gamification into e-learning programs is encouraged, as is the application of gamification techniques in teaching various courses, especially those related to language education. Finally, the research underscores the importance of incorporating educational game design principles and standards in the approval process for educational games to ensure alignment with educational objectives.